Pre-clinical study of curcumin in the treatment of gastric Cancer - Minghui Hao; Chungang Zhang (Journal of Functional Foods)
Gastric cancer is the fifth most common cancer globally and the third leading cause of cancer-related deaths. Researchers have been investigating natural compounds as potential alternatives to traditional cancer treatments, including surgery, radiation, and chemotherapy. One such compound is curcumin, which is derived from the rhizome of the turmeric plant. It possesses both edible and medicinal properties and has exhibited various biological activities that are beneficial for the treatment of gastric cancer. However, its clinical use is hindered by challenges such as poor water solubility, low bioavailability, and rapid metabolism. This review aims to summarize the mechanisms through which curcumin affects gastric cancer in both laboratory and animal studies, while also discussing effective strategies for enhancing its therapeutic application.